Efektivitas Kebijakan SAT POL PP Dalam Menciptakan Keamanan Studi Kasus Di Kecamatan Tebing Tinggi Dan Kecamatan Pendopo - Hestian, Yopan; Hartawan, Hartawan; Saputra, Wendi Aji (STIE Amkop Makassar, Indonesia, 2025)
This research was motivated by criminal incidents in Empat district Crime attacks such as muggings and forcible confiscations. Empat Lawang Regency geoverment has formed a security team, namely the Police Village Civil Service then this research aims to discuss Effectiveness of Civil Service Police Unit Policies in creating security in Tebing Tinggi District and Pendopo District. The theory used is a theory from William Dunn, there are 4 indicators, namely policy effectiveness Efficiency, Adequacy, Responsiveness and Accuracy. This research uses descriptive method with a qualitative approach. The results of this research show that there are 3 values that are met first Responsiveness indicator, the speed of responding to reports from the public and it has been effective. The second indicator of equality is the implementation of police unit policies the village civil service is effective. The three indicators of accuracy, unit policy village civil service police in creating security in the Tebing Tinggi sub-district has been effective so that people are safe and comfortable. But there are 2 from first indicator that has not been met is the efficiency indicator, namely the cost problem operational funds that do not exist every month. Second, adequacy in facilities from lighting the guard post to safety equipment when carrying out guard the post. Keywords: Effectiveness, Policy, Security.